Characters and values in mathematics teaching and learning: A review of research in Indonesia - Sofyan Mahfudy; Kamirsyah Wahyu; Mauliddin Mauliddin; Lalu Sucipto; Erpin Evendi; Samsul Irpan (Beta: Jurnal Tadris Matematika, 2019)
[English]: This article aims to critically review researches on characters and values in mathematics teaching and learning. Data for the review was the research articles authored by Indonesian mathematics education researchers and published in the online peer-review journals. The articles were searched in national scientific databases, DOAJ, and Google Scholar. The searches resulted in forty articles which aim to develop students' character and values through mathematics lesson. Five steps, i.e., text interpretation, coding, analysis, discussion, and reconsideration, are employed to analyze the articles qualitatively. The review reveals the articles lack of theoretical basis in the conceptualization of character/values, the development of character/values, and their measurement. Twenty-six articles on character did not define the notion clearly; meanwhile, the other articles only cite some definitions, but no operational definition was made. Character is a multifaceted construct which requires an operational definition to measure its development. In developing character and values, various strategies were utilized, but the most authors have not addressed theoretical analysis and rationale on their feasibility and relations the conceptualization of the notions. All articles did not provide any explanation on whether the instruments used were developed with respect to the nature of character or values development and fulfill psychometric properties. In this case, we argue that the researches were unfocused and not extensive. In this article, related theories and prior works are thoroughly discussed to shed light on the researching topics. Further research which relates to character education program in Indonesia is also elaborated. Keywords: Review, Character, Values, Mathematic teaching [Bahasa]: Artikel ini bertujuan mengulas secara kritis penelitian terkait karakter dan nilai dalam pembelajaran matematika. Data untuk ulasan merupakan artikel hasil penelitian yang ditulis oleh peneliti pendidikan matematika Indonesia dan diterbitkan di jurnal daring yang sudah melalui ulasan sejawat. Artikel dicari melalui basis data ilmiah nasional, DOAJ, dan Google Scholar. Pencarian menghasilkan 40 artikel yang bertujuan membangun karakter dan nilai siswa dalam pembelajaran matematika. Artikel dianalisis secara kualitatif melalui lima langkah yaitu interpretasi teks, penyusunan kode, analisis, diskusi, dan pertimbangan kembali. Ulasan menunjukkan bahwa artikel tersebut memiliki kekurangan dasar teoritis dalam konseptualisasi karakter/nilai, pengembangan karakter/nilai, dan aspek pengukuran. Dua puluh enam artikel yang membahas karakter tidak mendefinisikan istilah tersebut dengan jelas, sedangkan artikel yang lain hanya mengutip beberapa definisi tetapi tidak membuat definisi operasional. Karakter memiliki makna yang bervariasi sehingga membutuhkan definisi operasional untuk mengukur perkembangan pada diri siswa. Dalam mengembangkan karakter dan nilai, beragam strategi digunakan tetapi kebanyakan penulis tidak menjelaskan analisis teoritis and rasionalisasi kenapa strategi tersebut dapat digunakan dan berkaitan dengan konseptualisasi karakter/nilai. Semua artikel tidak memberikan penjelasan apakah instrumen yang dikembangkan sesuai dengan karakteristik perkembangan karakter atau nilai dan memenuhi kriteria psikometri. Dalam hal ini, penelitian terkait karakter/nilai tersebut belum fokus dan berskala kecil. Dalam artikel ini, beberapa teori yang relevan dan hasil penelitian sebelumnya dijelaskan secara mendalam untuk memberikan arah penelitian topik tersebut. Penelitian lebih lanjut yang berkaitan dengan program pendidikan karakter di Indonesia juga dibahas. Kata kunci: Analisis, Karakter, Nilai, Pembelajaran Matematika